2005
DOI: 10.1107/s0108270105008978
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomerohedrally twinned crystal structure of 2,3-diphenylbuta-1,3-diene

Abstract: The title compound, C 16 H 14 , is twinned by reticular pseudomerohedry of twin index 2. The primitive monoclinic cell of the single crystal can be transformed into a B-centred pseudoorthorhombic supercell with a fourfold volume. The twofold twin operation about the reciprocal a* axis of the primitive monoclinic cell is co-directional with the approximate C 2 axis of the molecule and a symmetry element of the orthorhombic supercell. A tentative twin domain model is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The reason might be that, as we reported earlier, the crystal structure is subject to reticular pseudomerohedral twinning. [17] The molecular structure is depicted in Figure 2, while important bond lengths and torsion angles are compiled in Tables 1 and 2, respectively. In the pseudo C 2 symmetric structure the compound adopts a butterfly-like geometry with a face-to-face like arrangement of the phenyl groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason might be that, as we reported earlier, the crystal structure is subject to reticular pseudomerohedral twinning. [17] The molecular structure is depicted in Figure 2, while important bond lengths and torsion angles are compiled in Tables 1 and 2, respectively. In the pseudo C 2 symmetric structure the compound adopts a butterfly-like geometry with a face-to-face like arrangement of the phenyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Computational Methods: Both MP2 and SCF calculations were performed with GAMESS-UK version 7.0, [31] employing the 6-311G* basis set. The minima were characterized by a Hessian calculation; no imaginary frequencies were found.…”
Section: Methodsmentioning
confidence: 99%
“…Unsubstituted 2,3-diphenylbutadiene was previously found to adopt a somewhat surprising s-gauche conformation in the solid state, with a torsion angle of 55.61 around the butadiene single bond. 37,38 MP2 and DFT calculations supported that this compound possesses an s-gauche minimum, and also revealed the presence of an s-trans minimum, which is somewhat (depending on the calculation method up to 1.47 kcal mol À1 ) higher in energy. 38,39 The structures of DA1 and DA2 were investigated with 6-311G** DFT/B3LYP calculations.…”
Section: Molecular Structuresmentioning
confidence: 69%
“…Depending on the degree of preservation of these conjugation paths, 1 and its functionalized derivatives will resemble either a substituted butadiene, an α,α-coupled bistyrene or a mixture thereof. Accordingly, the crystal structure of 1 reported by van Walree is best described as a system which retains much of the styrene conjugation but still shows some butadiene conjugation …”
Section: Introductionmentioning
confidence: 99%
“…In the course of their studies of branched π conjugated systems, van Walree and co-workers recently reported on the molecular and electronic structure of 2,3-diphenylbutadiene 1 . , In earlier work, the same authors reported on evidence for charge transfer (CT) in 2-(4-cyanophenyl)-3-(4- N , N -dimethylaminophenyl)-butadiene ( 2 ) along the bifurcated (i.e. cross-coupled) π system of butadiene, indicating that these compounds may be used in the development of materials with multiple conduction channels .…”
Section: Introductionmentioning
confidence: 99%